2010
DOI: 10.1103/physrevb.81.075207
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, vibrational, and thermodynamic properties of ZnS with zinc-blende and rocksalt structure

Abstract: We have measured the specific heat of zincblende ZnS for several isotopic compositions and over a broad temperature range (3 to 1100 K). We have compared these results with calculations based on ab initio electronic band structures, performed using both LDA and GGA exchangecorrelation functionals. We have compared the lattice dynamics obtained in this manner with experimental data and have calculated the one-phonon and two-phonon densities of states. We have also calculated mode Grüneisen parameters at a numbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 83 publications
13
31
0
Order By: Relevance
“…www.ann-phys.org A curious feature is that our calculations suggest a non-linear behavior of the Raman and IR active modes under pressure in both spinels (see available, but recent works from Cardona et al [28,29] found a good agreement between experimental data and similar ab initio results in binary compounds.…”
Section: Resultssupporting
confidence: 76%
“…www.ann-phys.org A curious feature is that our calculations suggest a non-linear behavior of the Raman and IR active modes under pressure in both spinels (see available, but recent works from Cardona et al [28,29] found a good agreement between experimental data and similar ab initio results in binary compounds.…”
Section: Resultssupporting
confidence: 76%
“…Like in some of our previous work 51, 52 we have investigated the dependence of C p /T 3 on the isotopic masses of the two components of cinnabar and compared our experimental data with the theoretical results. Fig.…”
Section: Specific Heatmentioning
confidence: 90%
“…We had realized in past work that the calculated phonon frequencies could depend considerably on SO interaction in materials containing heavy ions (Bi, PbTe, HgTe). [50][51][52] Since mercury falls in this category, we performed a few calculations of phonon frequencies taking SO interaction and the relaxed lattice parameters (cf. Table I) into account.…”
Section: Phonon Propertiesmentioning
confidence: 99%
“…Finally we would like to mention that, in accordance with corresponding remarks made in the Appendix D, it appears adequate and necessary to envisage with respect to forthcoming analyses also applications of the representative hybrid model (displayed in Section 2) by admitting constellations with more than three Einstein oscillators. This concerns in particular forthcoming analyses of very fine and sufficiently comprehensive C p (T) data sets available for several cubic II-VI materials like those presented by Cardona et al [95] for the group of zincblende-type mercury chalcogenides (b-HgS, HgSe, and HgTe) and the novel C p (T) data published recently by Cardona et al [96] for ZnS. Detailed analyses of the respective high-accuracy C p (T) data sets [95,96] within the frame of the duly flexible hybrid model (Section 2) offers then also the perspective of more incisive comparisons of resulting parameter sets with the theoretically calculated PDOS spectra presented in these papers.…”
Section: Iii-v Materialsmentioning
confidence: 98%